Communication and coordination across event phases: A multi‐team system emergency response. Issue 3 (4th May 2021) - Brown, Olivia; Power, Nicola; Conchie, Stacey M.
Abstract : This paper explores how multi‐agency response teams communicate and coordinate in different phases of a simulated terrorist incident. Procedural guidelines state that responders should coordinate their response to a major emergency across two phases: 'response' (when the incident is ongoing) and 'recovery' (when the threat has subsided, but the legacy of the incident is ongoing). However, no research has examined whether these phases map to the behaviours of responders in situ. To address this, we used measures of communication and coordination to examine how behaviours evolved during a simulated terrorist incident in the United Kingdom. We grounded our approach within the theoretical literature on multi‐team systems. It was found that the current response/recovery classification does not fit the nuanced context of an emergency. Instead, a three‐phase structure of 'response/resolve/recovery' is more reflective of behaviour. It was also found that coordination between agencies improved when communication networks became less centralized. This suggests that collaborative working in multi‐team systems may be improved by adopting decentralized communication networks. Practitioner points: To better prepare responders for emergencies, we recommend a three‐phase structure of 'response/resolve/recovery' is introduced in place of the current guidelines that outline a two‐phase structure of response and recovery. A three‐phase structure more accurately describes the behaviours of responders during emergencies and accounts for the shift in urgency between an ongoing incident (response) and shortly afterwards when the immediate threat has subsided (resolve). Given the cognitive load on focal agencies, decentralized communication structures should be introduced in the early phases of an emergency to increase collaborative decision‐making across inter‐agency partners.